2007
DOI: 10.1243/09576509jpe340
|View full text |Cite
|
Sign up to set email alerts
|

Self-starting capability of a Darrieus turbine

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 3 publications
4
70
0
1
Order By: Relevance
“…Despite this perception, it has been increasingly reported that the turbine can self-start in even its simplest configuration of fixed-pitch, straight blades with a symmetrical aerofoil section [3][4][5][6][7]. These conflicting perceptions and observations indicates that there may be a physical aerodynamic mechanism which is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this perception, it has been increasingly reported that the turbine can self-start in even its simplest configuration of fixed-pitch, straight blades with a symmetrical aerofoil section [3][4][5][6][7]. These conflicting perceptions and observations indicates that there may be a physical aerodynamic mechanism which is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the latter is better suited to the urban environment where wind direction rapidly changes as it is insensitive to wind direction. However, Darrieus (vertical-axis) turbines are commonly believed to be non self-starting [1,2].Despite this perception, it has been increasingly reported that the turbine can self-start in even its simplest configuration of fixed-pitch, straight blades with a symmetrical aerofoil section [3][4][5][6][7]. These conflicting perceptions and observations indicates that there may be a physical aerodynamic mechanism which is not well understood.…”
mentioning
confidence: 99%
“…Although Darrieus wind turbine was previously known for its difficulty in self-start [13][14][15], recent studies have shown that there are certain conditions that can make it otherwise. According to the recent literature on self-starting ability of the H-Darrieus wind turbine, Dominy et al [16] and Hill et al [17] demonstrated that it is possible to have a self-start three-bladed H-rotor VAWT using Figure 1. Wind profile in the internal boundary layer in a built environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kirke [19] reported that the self-starting torque and low speed torque problem of VAWTs can be overcome either by passive variable pitch or by a combination of suitable blade airfoil sections. Dominy et al [16] asserted that a lightly loaded, three-bladed rotor always has the potential to self-start under steady wind condition. Similar studies on the self-starting ability of VAWTs are reported in [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…NACA0012, and in the NACA0030 the forces are 150%higher than in NACA0012.The thicker blades are able to provide the wind turbine the self-start capabilities, while the thinner blade wind turbines are observed most likely unable to self-start [14,15].The NACA0030 present 26% better performance than NACA0012 [13].…”
Section: Introductionmentioning
confidence: 99%